PENDAMPINGAN PASTORAL TERHADAP PECANDU NARKOBA DI YAYASAN REHABILITASI RUMAH DAMAI SEMARANG - Elitri Santi Zebua; Yusup Rogo Yuono; Chlaodhius Budianto; Agung Dian Rengganis; Daryanto (SAGACITY : Journal of Theology and Christian Education, 2022)
This research is about pastoral dependence on drug addicts which was carried out by the Rumah Damai Rehabilitation Foundation in Semarang to help and assist people who help in drugs, with their aim to appreciate and receive and experience love as in the Peace House Rehabilitation Foundation that “My Family is My Home. " With a mission to build people with strong character and ready mentally and spiritually, through healing past wounds and family relationships. As for the pastoral assistance carried out by the Peace House Foundation, namely: conducting teaching, counseling, and paying attention to their development through physical healing and restoration of their soul and character with the aim of preparing their mentality to return intact among the family and community. With descriptive qualitative research method using literature review and field data. With the way the treatment carried out by the Rumah Damai Rehabilitation Foundation for the participants it served, it had a very positive impact, the result is that some of the staff currently serving at the Rumah Damai Rehabilitation Foundation are drug addicts who have made a full recovery. The Rumah Damai Rehabilitation Foundation can play a role and do good in helping to foster and approach pastoral care to heal and overcome drug addicts from the past and guide them to live according to God's word.